Assessing the impact of waste co-incineration at the Anhovo cement plant (Slovenia) on the regional cancer burden* - Zadnik, Vesna (Radiology and oncology (Ljubljana), 2025)
This epidemiological study aims to assess the cancer risk potentially associated with environmental exposure resulting from cement production and waste co-incineration at the Anhovo cement plant in Western Slovenia and to develop a strong and reliable methodological framework for the long-term surveillance of environmentally related cancer risks in small geographical areas. Materials and methods We integrated all the available data sources: cancer cases from the population-based Slovenian Cancer Registry; background population; and available measurements on exposure to air PM10 particles and chromium (Cr) in the soil in the municipality of Kanal and the wider Goriška region. Relative risks of cancer in small geographical areas were estimated using Bayesian hierarchical spatial models and the population attributable fractions of the modelled risk factors were calculated. The point source analysis compared the cancer risk near the cement plant to that in more distant areas. Results The analysis did not reveal any excess cancer incidence in the area of the Anhovo cement plant or an association with the PM10 particles and Cr in the soil. The incidence of mesothelioma remains high in the region, but stable in the last two decades. Conclusions In view of the environmental pollution caused by either historical cement production or the potential impact of current waste co-incineration activities in Kanal, we strongly recommend that a follow-up epidemiological study be carried out in the next 10 to 20 years. The methodological framework established in the present study provides a foundation for the ongoing surveillance of the cancer burden in the region.
Keywords: cancer data; cancer incidence; environmental exposure; okoljska tveganja; pojavnost raka; register raka